Chadecja w PRL? Czy politycy katoliccy byli chrześcijańskimi demokratami? - Skibiński, Paweł (Pamięć i Sprawiedliwość, 2017)
In the period of 1945–1989, in Communist Poland, after the subjection of the Labour Party by the Communists in 1945, and their assimilation in 1950 by the Democratic Party, there was no independent Christian Democratic party; despite this, Poland was a country of the Soviet Block, in which the Catholic Church had relatively large freedom, while Christian democratic parties officially existed in GDR and the Czechoslovakian Republic. This issue is strictly related with several other matters: with Christian Democratic and non-Christian democratic efforts of the Catholics aimed at the establishment of the Catholic Party inside the PRL political system (among others, on the basis of Bolesław Piasecki’s PAX Association); with the activities of the groups relating to the Christian democracy outside the party structures (here it necessary to mention Janusz Zabłocki, the ODiSS group and Polish Catholic Social Association); with activities of all other groups of “lawful” Catholics functioning within Communism; finally with the issue of intellectual research aimed at the rationalisation of the existence of Christian democracy outside the democratic system, in the necessary cooperation with an atheistic totalitarian regime (here a special role was played by inspiration with Christian socialism of Emmanuel Mounier). To provide the final statement concerning the scale of the Christian democratic inspiration in both social and political life it is necessary to deepen the present research concerning almost every political groups of Catholics in PRL – both legal and illegal – maybe aside from the well-known group of “Znak”. It is necessary to verify the findings of the present historiography, which mainly belonged to the identity stream, that is the stream giving priority for the justification of the political attitudes of Catholics during PRL over comprehensive and reliable information analysis. The matters crucial for understanding the existence context of the Christian democratic inspirations in the period of PRL include the issues of various forms of political Catholic realisms in PRL (including specific differentiation of the realism of resistance, collaboration and capitulation – using terms applied by Rafał Matyja), as well as an explanation as to why Catholic groups in PRL – in contrast to the Christian Democrats during the inter-war period – tried to build their identity on the critique of the largest Catholic political formation in Poland – namely the national movement, and often even broader – on the critique of the entire relation between Catholicism and Polish national identity.